On Research Libraries Statement and Recommendations of the Committee on Research Libraries of the American Council of Learned Societies, Submitted to National Advisory Commission on Libraries - Burkhardt, Frederick; National Advisory Commission on Libraries, Washington, DC.; American Council of Learned Societies, New York, NY. (Washington : Distributed by ERIC Clearinghouse, 1967)
This report on the needs of research libraries with recommendations for improvement is based on minutes of meetings of the Committee on Research Libraries and commissioned papers on topics of major concern. Problems of research libraries involve: (1) increased demands because of rising university population, new business and industrial information needs, extensive government research, and a wider scope of scholarship, (2) inadequate acquisition, cataloging and bibliographic apparatus, (3) preservation of materials, (4) staff, (5) library costs, and (6) automation. A major conclusion is that the nation's research libraries need greater assistance from both government and private sectors to respond effectively to increasing demands. A national library system is proposed that will require major federal leadership and support and will involve the creation of a national commission on libraries to be concerned with establishing the library system, advising the government on library needs, and planning and coordinating in the areas of acquisitions, bibliography, and technology. Other areas covered by specific recommendations are: the Library of Congress, the Center for Research Libraries, durable paper, and all types of financial support. Included are the complete texts of three commissioned papers, covering bibliographical control, technology, and the federal government. A discussion of copyright is appended. (JB)
Microfiche.
Keywords: Automation